Two-dimensional effects in Fowler-Nordheim field emission from transition metal dichalcogenides. (May 2019) - Urban, F; Passacantando, M; Giubileo, F; Iemmo, L; Luongo, G; Grillo, A; Di Bartolomeo, A
Abstract: We report field emission from bilayer MoS 2 and monolayer WSe 2 synthesized by CVD on SiO 2 / Si substrate. We show that the emitted current follows a Fowler-Nordheim model modified to account for the two-dimensional confinement of charge carriers. We derive the figures of merit of field emission and demonstrate that few-layer transition-metal dichalcogenides are suitable for field emission applications.